Synthesis of 2-, 3- and 4-Carboxyphenoxyacetic Acid: A Necessary Modification - Mohan Adak, Mohini (Asian Journal of Chemistry, 2010)
Selective esterification of aliphatic primary carboxy groups over the aromatic ones within the same framework of a molecule needed 2-, 3- and 4-carboxyphenoxyacetic acids which where synthesised in very good yield, by slight modification of the method introduced hundred years back. Condensed product from chloroacetic acid and corresponding hydroxybenzaldehyde was separated from the mixture as methyl or ethyl ester and subsequently oxidised by alkaline KMnO4. Acidification and usual work up generated the desired products in good quality.